2023
DOI: 10.1109/access.2023.3252916
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Models for Stable Gait Prediction Applied to Exoskeleton Reference Trajectories for Children With Cerebral Palsy

Abstract: Gait trajectory prediction models have several applications in exoskeleton control; they can be used as feed-forward input to low-level controllers and to generate reference/target trajectories for position-controlled exoskeletons. In our study, we implement four deep learning models (LSTM, FCN, CNN and Transformer) that perform one-step-ahead gait trajectory prediction after training on gait patterns of typically developing children. We propose a methodology that optimises for stability in long-term forecasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In a previous study of ours, the fully connected neural network (FCNN) demonstrated low errors in both short-term and long-term gait trajectory prediction tasks and exhibited higher robustness to added noise [ 33 ]. These were the reasons for selecting the FCNN for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of ours, the fully connected neural network (FCNN) demonstrated low errors in both short-term and long-term gait trajectory prediction tasks and exhibited higher robustness to added noise [ 33 ]. These were the reasons for selecting the FCNN for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The models were trained for 70 epochs, with training being terminated earlier (using the early stopping method) if the DTW distances on the validation set did not decrease for 20 epochs. In our previous study [ 33 ], we elaborated on how DTW distances are used to optimise gait trajectory prediction models.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing the angle of hip and knee joints and plantar pressure data, Wu et al used a graph convolutional network model to classify the gait phase for a lower limb exoskeleton robot [ 27 ]. For children with cerebral palsy, Kolaghassi et al implemented four deep learning models (LSTM, FCN, CNN and a transformer) to predict joint angles and proposed an approach for adaptive trajectory generation based on a dataset consisting of flexion–extension angles of the hip, knee and ankle in the sagittal plane [ 28 ]. Huang et al attached an intelligent inertial measurement unit (IMU) to the surface of a shoe to sample the acceleration data of foot movements and proposed an online detection algorithm to identify the gait phase [ 29 ].…”
Section: Related Workmentioning
confidence: 99%
“…The primary focus of existing ML models for 3DGA in children lies in gait classification ( Kamruzzaman and Begg, 2006 ; Zhang et al, 2009 ; Zhang and Ma, 2019 ; Choisne et al, 2020 ; Khaksar et al, 2021 ) rather than the development of models for predicting gait time series. There are only a handful of studies focused on predicting children’s gait using ML techniques ( Kwon et al, 2012 ; Vigneron et al, 2017 ; Morbidoni et al, 2021 ; Kolaghassi et al, 2022 ; Kolaghassi et al, 2023 ). A research group used EMG sensors’ signals to predict children with cerebral palsy (CP) knee moment and achieved high correlation coefficients between 0.71 and 0.93 for different participants ( Kwon et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study proved the feasibility of using neural networks in predicting gait events from surface EMG signals in hemiplegic cerebral palsy ( Morbidoni et al, 2021 ). Other studies have employed ML techniques to estimate one-step-ahead gait trajectories to control lower-limb robotic devices in children with CP ( Kolaghassi et al, 2022 ; Kolaghassi et al, 2023 ). However, none of the mentioned studies utilized IMUs’ data to develop the ML model.…”
Section: Introductionmentioning
confidence: 99%